2014
DOI: 10.1007/s10533-013-9944-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of steady-state in the global biogeochemical Si cycle: emerging evidence from lake Si sequestration

Abstract: Weathering of silicate minerals releases dissolved silicate (DSi) to the soil-vegetation system. Accumulation and recycling of this DSi by terrestrial ecosystems creates a pool of reactive Si on the continents that buffers DSi export to the ocean. Human perturbations to the functioning of the buffer have been a recent research focus, yet a common assumption is that the continental Si cycle is at steadystate. However, we have no good idea of the timescales of ecosystem Si pool equilibration with their environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 172 publications
(159 reference statements)
5
62
0
1
Order By: Relevance
“…Frings et al (2014a) highlight the effectiveness of lacustrine environments in retaining DSi in sediments via the bSiO 2 pump, which on a global scale can translate to a net export of between 21 and 27% of river DSi export. This equates to an estimation of 1.53 Tmol yr −1 (Frings et al, 2014a) (Figure 1). These data highlight the challenges in underpinning global estimates of lake biogeochemical cycling (particularly for large lakes and reservoirs) to better constrain the evolution of the global biogeochemical cycling of Si.…”
Section: Challenges In Interpreting Lake Geochemistry and Palaeolimnomentioning
confidence: 95%
See 2 more Smart Citations
“…Frings et al (2014a) highlight the effectiveness of lacustrine environments in retaining DSi in sediments via the bSiO 2 pump, which on a global scale can translate to a net export of between 21 and 27% of river DSi export. This equates to an estimation of 1.53 Tmol yr −1 (Frings et al, 2014a) (Figure 1). These data highlight the challenges in underpinning global estimates of lake biogeochemical cycling (particularly for large lakes and reservoirs) to better constrain the evolution of the global biogeochemical cycling of Si.…”
Section: Challenges In Interpreting Lake Geochemistry and Palaeolimnomentioning
confidence: 95%
“…Lakes, in addition to the soil-vegetation system, play an important role in buffering continental DSi export to the oceans. Previous assumptions were that this buffering capacity of the continental Si cycle was in steady-state; however, this has now been challenged (Frings et al, 2014a). Frings et al (2014a) highlight the effectiveness of lacustrine environments in retaining DSi in sediments via the bSiO 2 pump, which on a global scale can translate to a net export of between 21 and 27% of river DSi export.…”
Section: Challenges In Interpreting Lake Geochemistry and Palaeolimnomentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, evidence arises that BSi pools are in disequilibrium at decadal timescales due to disturbances and perturbations by humans, e.g., by changes in forest management or farming practices (Barão et al, 2014;Keller et al, 2012;Vandevenne et al, 2015). As a consequence, BSi accumulation and BSi dissolution are not balanced, which influences Si cycling in terrestrial biogeosystems, not only on decadal but also on millennial scales (Clymans et al, 2011;Frings et al, 2014;Sommer et al, 2013;Struyf et al, 2010). Sommer et al (2013), for example, found the successive dissolving of a relict phytogenic Si pool to be the main source of dissolved Si in soils of a forested biogeosystem.…”
mentioning
confidence: 99%
“…changes in productivity, climate, precipitation and nutrient supply). In lacustrine sediment cores, BSi content can range from the detection limit (0.01 wt %) to > 70 wt % SiO 2 (Frings et al, 2014a). The downcore variations in BSi through time vary from as little as 2 wt % SiO 2 (Adams and Finkelstein, 2010;Ampel et al, 2008) to a high of 10-40 wt % SiO 2 (Johnson et al, 2011;Prokopenko et al, 2006;Van der Putten et al, 2015) and depends on several interacting factors such as mineral matter or organic matter accumulation, diatom productivity and preservation/dissolution processes.…”
Section: Implications For Palaeoecological Studiesmentioning
confidence: 99%